Effects of Magnetic Stimulation on Dental Implant Osseointegration: A Scoping Review - Gennaro Cecoro; Debora Bencivenga; Marco Annunziata; Nunzio Cennamo; Fulvio Della Ragione; Alessandro Formisano; Angelantonio Piccirillo; Emanuela Stampone; Pio Antonio Volpe; Luigi Zeni; Adriana Borriello; Luigi Guida (Applied Sciences, 2022)
This PRISMA-ScR driven scoping review aims to evaluate the influence of magnetic field stimulation on dental implant osseointegration. Seven databases were screened adopting ad-hoc strings. All clinical and preclinical studies analyzing the effects of magnetic fields on dental implant osseointegration were included. From 3124 initial items, on the basis of the eligibility criteria, 33 articles, regarding both Pulsed ElectroMagnetic Fields (PEMF) and Static magnetic Fields from permanent Magnets (SFM) were finally included and critically analyzed. In vitro studies showed a positive effect of PEMF, but contrasting effects of SFM on bone cell proliferation, whereas cell adhesion and osteogenic differentiation were induced by both types of stimulation. In vivo studies showed an increased bone-to-implant contact rate in different animal models and clinical studies revealed positive effects on implant stability, under magnetic stimulation. In conclusion, although positive effects of magnetic exposure on osteogenesis activity and osseointegration emerged, this scoping review highlighted the need for further preclinical and clinical studies. More standardized designs, accurate choice of stimulation parameters, adequate methods of evaluation of the outcomes, greater sample size and longer follow-ups are needed to clearly assess the effect of magnetic fields on dental implant osseointegration.